Discussing death: Making end of life implicit or explicit in paediatric palliative care consultations. Issue 2 (February 2019) - Ekberg, Stuart; Danby, Susan; Rendle-Short, Johanna; Herbert, Anthony; Bradford, Natalie K.; Yates, Patsy
Highlights: Many clinicians and researchers advocate explicitly discussing death. There are, however, few studies of real-world conversations about death. This study uses video-recorded paediatric palliative care consultations. Typically, death was made implicit during discussions of this matter. Moreover, explicitly mentioning death was not necessary to discuss it. Abstract: Objective: To consider whether and how family members and clinicians discuss end of life during paediatric palliative care consultations. Methods: Nine naturally occurring paediatric palliative care consultations were video recorded and analysed using conversation analytic methods. Analysis: Focusing on three consultations in which end of life was treated as a certain outcome, analysis explored ways in which end of life was made either implicit or explicit within these consultations. Our analysis suggests that end of life was made explicit when: 1) ancillary to the current focus of discussion, 2) in relation to someone else's child, or 3) specifically relevant to the local context of the discussion. More commonly, in all other instances in the data, end of life was made implicit during discussions relating to this matter. Conclusion: This preliminary research indicates that the local context of a conversation can influence how end of life is mentioned and discussed. Practice implications: Clinicians often are encouraged to promote honest and 'open' discussions about end of life. Our findings show that it is not necessary to explicitly mention end of life in order to discuss it.